Optimizing worker safety: A case study on lifting load and body posture in rice warehouse operations - Dewantari, Nustin Merdiana; Taqdisillah, Creavilian; Mangaranap, Reefly Yoshea; Mariawati, Ade Sri; Herlina, Lely (Journal Industrial Servicess, 2024)
A rice warehouse's operations consist of loading and unloading activities of rice from transport trucks to storage warehouses and vice versa, distributing it to nearby agents. The work at the warehouse is done manually without any tools, with workers lifting rice sacks weighing more than 50 kg onto their shoulders every day. Tasks involving sudden loading pose a risk of musculoskeletal disorders (MSDs). The purpose of this study is to determine the safe weight that can be lifted by workers and to measure body posture to evaluate the risk of MSDs to prevent injuries. The NIOSH (National Institute for Occupational Safety and Health) method is used by measuring the Recommended Weight Limit (RWL) and Lifting Index (LI). The REBA (Rapid Entire Body Assessment) method involves measuring body parts A and B using the REBA worksheet. The study results indicate that the Lifting Index score for rice lifting has a very high risk, as does the REBA work posture score, which also shows a very high risk. Therefore, immediate improvements are needed in the loading and unloading process.